Risk assessment of gas outburst in tunnels in non-coal formation based on the attribute mathematical theory. Issue 1 (1st January 2019) - Zhang, Kai; Zheng, Wenbo; Xu, Cong; Chen, Shougen
Abstract: Gas outburst can result in great loss of life and property during tunnel construction. Gas outburst in tunnels in non-coal formation is often more harmful than that in coal-bearing formation. In order to take effective countermeasures to prevent the occurrence of gas outburst during tunnel construction, it is essential to assess the risk of gas outburst before tunnel construction. This paper attempts to establish an assessment system for evaluating the risk of gas outburst in tunnels in non-coal formation in the survey phase of tunnelling based on the attribute mathematical theory. Based on the principle of relevance and operability, eight factors that influence the gas outburst in non-coal formation are selected as the attribute evaluation indices. Attribute measure functions are constructed to calculate the single index attribute measures for evaluation indices. The fuzzy Analytic Hierarchy Process is used to determine weights of evaluation indices. A confidence criterion is applied to recognize the risk grade of the evaluation object. The proposed attribute evaluation system is applied to assess the gas outburst risk in a tunnel in the survey phase. The evaluation results show good agreement with the practical situation of gas, verifying the applicability of this attribute assessment system.